1991
DOI: 10.1177/0093854891018002002
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Mediators of Aggression

Abstract: Although theoretical and empirical evidence suggests that cognitions play a significant role in shaping aggressive responses, causal relations between cognitions and other predictors of aggression (e.g., past behavior, arousal, personality traits) are unclear. This study attempted to predict aggression in an experimental setting, using the Ajzen-Fishbein Theory of Reasoned Action. Fifty-one patients in a federal forensic hospital role-played aggressive behavior. Independent measures included cognitive componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…While some researchers reported the existence of a link between the two (Andrews, 1996; Howells, 1989; Howells, 2004; Kroner et al 1992; Novaco, 1994; Walters, 1990; Welsh and Gordon, 1991; Zamble and Quinsey, 1997), others have disputed it (Loza and Loza-Fanous, 1999; Tice and Baumeister, 1993;). There are indications that the emotion of anger is an important influence on offending for some MSO, but the mechanisms that fuel this relationship remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…While some researchers reported the existence of a link between the two (Andrews, 1996; Howells, 1989; Howells, 2004; Kroner et al 1992; Novaco, 1994; Walters, 1990; Welsh and Gordon, 1991; Zamble and Quinsey, 1997), others have disputed it (Loza and Loza-Fanous, 1999; Tice and Baumeister, 1993;). There are indications that the emotion of anger is an important influence on offending for some MSO, but the mechanisms that fuel this relationship remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Note that although reasoned action has been used to understand alcohol use (Cooke, Sniehotta, & Schüz, 2007; Johnston & White, 2003; Marcoux & Shope, 1997) and aggression (Doane, Pearson, & Kelley, 2014; Roberto, Meyer, Boster, & Roberto, 2003; Tolman, Edleson, & Fendrich, 1996; Welsh & Gordon, 1991) as independent outcomes, we apply it to their combination as a single behavior (Bleakley et al, 2017). Note that this is the kind of “risky” population and behavior that is also used in many prototype studies, so it is especially appropriate for a comparative analysis.…”
Section: Methods and Measuresmentioning
confidence: 99%
“…First examined is the proposition that cognitions, including irrational beliefs, may mediate criminal activity. In forensic patients, a cognitive mediation model of aggression has been supported by Welsh and Gordon (1991). However, the authors also found strong support for an alternative model that holds aggression to be a function of tension and trait anger, "independent of the cognitive components of the Ajzen-Fishbein model."…”
Section: Cognitions and Offending--the Logical Case For Rebt And Cbt mentioning
confidence: 97%